New Photometric Investigation of the Solar-Type Shallow-Contact Binary HH Bootis - Jia-jia He; Jing-jing Wang (Advances in Astronomy)
The short-period solar-type contact binary HH Boo was monitored photometrically for about 8 years. It is found that the CCD light curves in the B, V, R, and I bands obtained in 2010 are symmetric, while the multicolor light curves observed in 2011 and 2012 by several investigators showed a positive O’Connell effect where the maxima following the primary minima are higher than the other ones. This indicates that the light curve of the solar-type contact binary is variable. By analyzing our multicolor light curves with the Wilson-Devinney code (W-D code), it is confirmed that HH Boo is a W-type shallow-contact binary system with a mass ratio of q = 1.703(31) and a degree of contact factor of f = 12.86%(0.73%). By including 109 new determined times of light minimum together with those compiled from the literature, it is detected that the O-C diagram shows a cyclic oscillation with a period of T3 = 6.58(11) yr and an amplitude of A3 = 0.0018(1) d. The cyclic change may reveal the presence of an extremely cool third body orbiting the central binary.